Crippling of Webs with Partial Depth Stiffeners under Patch Loading - Salkar, Raghuvir; Salkar, Abhishek; Davids, William (Engineering Journal, 2015)
Chapter J of the 2010 AISC Specification recommends the use of either single-or double-sided minimum half depth transverse web stiffeners where web crippling strength is less than design concentrated load; use of a doubler plate of minimum half web depth is also suggested in the Specification. Commentary on the Specification mentions that since the web crippling phenomenon has been observed to occur in the web adjacent to the loaded flange, a half-depth stiffener (or stiffeners) or a half-depth doubler plate is needed to eliminate web crippling. Research conducted at the University of Maine, however, clearly showed that web crippling can occur even in webs having half depth stiffeners. Further, the AISC Specification does not have a formula to predict crippling strength of webs with partial depth stiffeners under local compressive loads. This paper presents a formula for evaluating crippling strength of webs with partial depth stiffeners which considers the effect of depth of stiffener, width of load, and eccentricity of loading.